Dermatomycosis in lower limbs of diabetic patients followed by Podiatry consultation - Parada, H. (2016)
BACKGROUND: Diabetic patients are particularly susceptible to fungal infections due to modifications that occur in their immunological system. These modifications compromise natural defences, such as skin and nails, especially from lower limbs. OBJECTIVES: Assessing the presence of dermatomycosis in lower limbs of Portuguese diabetic patients followed on Podiatry consultation. Determination of possible predisposing factors and the most frequent fungal species associated with the cases are included in the study. METHODS AND PATIENTS: A six-month prospective study was carried out in 163 diabetic patients with signs and symptoms of dermatomycosis followed by Podiatry at the Portuguese Diabetes Association in Lisbon. Samples from the skin and/or nails of the lower limbs were collected and demographic and clinical data of those patients were recorded. RESULTS: Trichophyton rubrum was the most frequently isolated dermatophyte (12.1%), followed by T. mentagrophytes (7.7%) and T. tonsurans (4.4%). Our study showed positive associations between type 2 diabetes and the presence of dermatomycosis in the studied population (p=0.013); also between the occurrence of dermatomycosis and localization of body lesion (p=0.000). No other predisposing factor tested was positively associated with infection (p>0.05). CONCLUSIONS: Data on superficial fungal infections in diabetic patients are scarce in Portugal. This study provides information on the characterization of dermatomycosis in lower limbs of diabetic patients.